The peculiarities and structure of educational work of physical training teacher - Halyna Honchar (Слобожанський науково-спортивний вісник, 2015)
Purpose: to analyze the peculiarities and structure of educational work of Physical training teacher. Material and Methods: during the research we used the method of literature analysis. Results: defined the peculiarities of educational work of physical training teacher. There were analyzed the types of teacher activities, different approaches to the structure of the study and its separate components. Basic requirements which are considered to be model features of mastering knowledge, abilities and skills, which in turn, provide professional effectiveness of teachers. Conclusions: this work allows to examine the depth of aspects which promote the potential unleashing of physical training teacher.